Gesundheitsforschung kommunizieren, Stakeholder Engagement gestalten Grundlagen, Praxistipps und Trends - Lesch, Wiebke; Schütt, Antje (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2017)
In view of a social development towards more transparency and participation, communication is becoming more and more important in (health) research. This anthology provides suggestions on how successful communication in health research can be designed and is a reference work that provides readers with help and tips for their own work. The most important facets of science communication in health research are presented: from the development of a communication strategy to the relationship between science and the media, to the creation of evidence-based information for patients, from questions of organizational communication to stakeholder engagement and fundraising.